Social Determinants of Health (Social Risk) and Nutritional Status Among Community-Dwelling Older Adults Living in a Rural Setting: The Atahualpa Project - Oscar H. Del Brutto; Denisse A. Rumbea; Robertino M. Mera; Bettsy Y. Recalde; Mark J. Sedler (SAGE Publishing, 2022)
Background: Several studies have attempted to clarify the role of social determinants of health (SDH) on nutritional status of older adults, but results are inconsistent due to differences in SDH assessments at different levels of population development. In this study, we assessed this association in community-dwelling older adults living in rural Ecuador. Methods: SDH were measured by the Gijon's Social-Familial Evaluation Scale (SFES) and nutritional status by the Mini Nutritional Assessment (MNA ® ). Multivariate logistic regression models were fitted to assess the association between SDH components and nutritional status. Locally weighted scatterplot smoothing (LOWESS) and a generalized linear model were used to evaluate the potential non-linearity of the association between the Gijon's SFES and MNA ® scores. Results: A total of 295 individuals (mean age: 72.1 ± 7.6 years; 58% women) were enrolled. There was an inverse association between the total Gijon's SFES and nutritional status (OR: 0.75; 95% C.I.: 0.65-0.86; P  < .001). Three of five components of the Gijon's SFES (family situation, social relationships, and support networks) were inversely associated with nutritional status in multivariate logistic regression models. A LOWESS plot, together with a generalized linear model, showed an inverse linear relationship between the continuous Gijon's SFES and MNA ® scores. One standard deviation of increase in the continuous Gijon's SFES score (2.39 points) decreased the MNA ® score by 0.78 points. Conclusion: Study results show a significant inverse association between high social risk and a good nutritional status. Components of the Gijon's SFES measuring social isolation are responsible for this association.